Menimbang Kesiapan Penerapan Carbon Pricing di Indonesia dengan Studi pada Kanada, Britania Raya, dan Australia - Hadijjah Ummini Elsa; Rachmad Utomo (JURNAL PAJAK INDONESIA, 2022)
The purpose of this study is to determine the advantages and disadvantages of carbon tax and the cap and trade scheme in carbon pricing. It is also to describe its implementation in several countries, namely Canada, Great Britain, and Australia. In addition, this study also describes Indonesia’s preparation for implementing carbon pricing and provides alternative factors that need to be considered by the government. This study uses a qualitative approach with comparative analysis studies in these countries. Data collection was carried out using the study literature method and interviewed several sources who have an interest in energy and carbon taxes. This study shows that the carbon tax and the cap and trade scheme have their respective advantages and disadvantages, so the decision of which carbon pricing instrument to apply is adjusted to each country’s needs. In general, the policies in the three countries have the same objectives, but the instruments, mechanisms, and tariffs imposed are different. The Indonesian government has prepared the implementation of carbon pricing since 2021, but until now the technical regulations related to its implementation had not yet been issued. There are still several alternative factors, namely: implementing regulations and other environmental policy regulations, determining optimal tariffs, redistribution of revenues, as well as alternative energy substitutes that are in accordance with community readiness to be considered by the Indonesian government in preparation for implementing carbon pricing.